MASLAHAT SEBAGAI METODE IJTIHAD DAN TUJUAN UTAMA HUKUM ISLAM - Ali Rusdi, Muhammad (DIKTUM: Jurnal Syariah dan Hukum, 2017)
Abstract: Maslahat is the main goal in Islam, Allah teaches down the teachings especially in the issue of Islamic law cannot be released for the benefit of human beings, although there is a difference in the nature of the benefit from the aspect of the source of maslahat, but the scholars agree in terms of the main purpose of Islamic law is jalb al-mashalih wa daru al-mafasid, how Islamic law can as much as possible provide benefits and goodness to humans while eliminating any possibility of damage and danger to humans.